THE EFFECT OF CHILDREN (Ocimum sanctum) LEAF EXTRACT ON BACTERIA GROWTH Staphylococcus aureus - Laboddu, Mohammad Andi (Journal of Health, Technology and Science (JHTS), 2023)
This research aims todetermine the effect of basil leaf extract (Ocinum sanctum) on the growth of Staphylococcus aureus and the optimal concentration of basil leaf extract (Ocinum sanctum) in inhibiting the growth of Staphylococcus aureus. This research method used a completely randomized design (CRD) with 5 treatments with 4 replications consisting of negative control (aquades), positive control (Amoxicillin), extract 20%, 40% and 60%. Research results obtained that basil leaf extract (Ocinum sanctum) has an effect on the growth of Staphylococcus aureus bacteria. The optimal concentration of basil leaf extract (Ocinum sanctum) in inhibiting the growth of Staphylococcus aureus bacteria is at a concentration of 40% with the category of "strong" bacterial inhibition. Keywords :Basil (Ocinum sanctum), Staphylococcus aureus, Extract, Bacteria